The Effect of Leader-Member Exchange(LMX), Organization-Based Self-Esteem and The Broad Role of Self-Efficacyon Predictors of Perception Employability - Akmal Akmal; Lala Irviana; Elfitra Azliyanti (Jurnal Manajemen Universitas Bung Hatta, 2023)
This study focuses on individuals as employees and their work-related capabilities. It emphasizes the need for individuals to take ownership of their professional development, acknowledge their employability, and adopt a contemporary career outlook that considers employability beyond their current organization. suggested that employability is an asset that can improve performance and flexibility. To explore the factors that influence employability perception, we tested five hypotheses: leader-member exchange, the broad role of self-efficacy, and organization-based self-esteem. Using regression analysis with SEM PLS, we analyzed data from 323 questionnaires, representing a response rate of 97.52%. Our findings indicate that leader-member exchange positively affects employability perception, organization-based self-esteem positively affects employability perception, and the role of self-efficacy positively affects employability perception. Additionally, leader-member exchange positively affects both organization-based self-esteem and the extent of the role of self-efficacy.